Biobanking in the hospital of a multidisciplinary research medical center as a potential for a wide research range. Part II. Specifics and first results of developing a described collection of biomaterial - O. V. Kopylova; A. I. Ershova; M. S. Pokrovskaya; A. N. Meshkov; A. L. Borisova; I. A. Efimova; Z. Z. Serebryanskaya; A. V. Pustelenin; Yu. V. Yuzkov; E. V. Garbuzova; A. M. Velichko; F. R. Sayfutdinov; et al. (Кардиоваскулярная терапия и профилактика)
In connection with the development of genetic and other types of research in translational medicine, collections containing a significant number of biospecimens and large data sets are required. Since in-depth examination of patients is most often carried out during hospitalization, the creation of collections based on electronic medical records (EMR) data is promising. In this regard, the project "Total biobanking in the hospital of the National Medical Research Center for Therapy and Preventive Medicine" was initiated, aimed at total biobanking of blood and related products from patients in inpatient departments and the creation of a unified system that combines information on biosamples, clinical and other types of data.Aim. To describe the collection of biospecimens collected within the project "Total biobanking in the hospital of the National Medical Research Center for Therapy and Preventive Medicine" for August 2023, and to analyze the process of biospecimen description.Material and methods. Recruitment of patients is carried out on the basis of inpatient departments of the National Medical Research Center for Therapy and Preventive Medicine, only if the patient signs informed consent. After blood is taken, the biomaterial enters the biobank, where sample preparation and storage is carried out, as well as data about each biosample is entered into a special FreezerPRO system. At the same time, clinical data about the patient is collected using EMR, which are combined in the Medialog medical information system.Results. A special software for data exchange between the medical information system and the biobank has been developed, which combines information about patients entering the Medialog medical information system and the FreezerPro biospecimen management system, which contains detailed information about biospecimens. As of August 25, 2023, biomaterial from 3996 patients was collected, which was accompanied by a detailed clinical summary. In particular, data is available on diagnoses (for 100% of patients), laboratory test data (100%), paraclinical data, in particular, electrocardiography (100%), echocardiography (76,8%), 24-hour Holter monitoring (59,8%), esophagogastroduodenoscopy (27,3%), etc. The most common diseases were hypertension (76,0%), atherosclerosis (69,9%), coronary artery disease (52,9%), arrhythmias (50,6%), diabetes (19,2%). In addition, 25,0% of patients had prior stenting.Conclusion. Total biobanking within the hospital of a multidisciplinary research medical center allows for the rapid and high-quality collection of biomaterial and related data. A collection of biospecimens with comprehensive and detailed clinical annotations has been collected. A primary analysis of the collection was carried, which showed that it can be used for a wide range of studies.